TO THE PROBLEM OF PHYTO-AMELIORANTS INFLUENCE ON THE PRODUCTIVITY OF THE RE-SALTED LANDS IN THE SOUTH KAZAKHSTAN REGION - D. Sunakbaeva, (Academic Journal of Physical and Chemical Sciences, 2019)
The green cover of the planet is the most valuable of man's achievements. But in spite of this, until now not all the possibilities of plants have been taken into account and used by mankind. The main cultivated plants were domesticated several thousand years before our era. The ways of optimal artificial regulation of plant ontogeny are still unknown, which without pathogenetic consequences can lead to their maximum productivity. The establishment of ways to regulate plant ontogeny - which is extremely important for harvest programming taking into account the fertility of soils - is associated with the establishment of regularities that allow regulating photosynthesis, periodicity and dynamics of growth, nitrogen exchange. At present, the state of the vegetative cover of the Earth is deteriorating. The main reason is diversity and different directions of pathological phenomena that occur in plants. Pathological phenomena are combined into three categories: pathological reactions, pathological processes and diseases. The most dangerous are the violations that lead to the complete or partial disappearance of certain plant species. The reasons for the disappearance of plants are diverse. They can be related not only to man's anthropogenic activities, but also to certain natural disasters. The most important of them are: 1) physical extermination for agricultural and forestry purposes, for mining, construction and industrial production. The results of the research showed that phytomelioration is a set of measures to improve the state of the environment through the production or maintenance of natural plant communities. Improving the utilization of irrigated lands by phytomelioration is also environmentally and economically viable.